Pemberdayaan Masyarakat Desa Pasir Tanjung Melalui Optimalisasi Edu-Tani untuk Mencapai Pembangunan Desa Berkelanjutan - Andani, Gita Putri; Resti Rahmawati Putri; Muhammad Nafiz; Hani 'Athiyya Rafi; Siagian, Putri Junita; Luzicoiij, Michael Edison; Rava Raisha Putra; Dzihan Dinar Rabani; I Made Artika; Gita Putri Andani (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
The Thematic Community Service Lecture (KKNT) activity held in Pasir Tanjung Village, Tanjungsari District, Bogor Regency aims to empower the Pasir Tanjung Village community to support sustainable village development through the edu-tani optimization program. This activity was carried out using a method involving socialization, demonstration, mentoring, and cooperative learning in several programs: making liquid organic fertilizer (Green Craft), natural pesticides (Integrated Pest Management), agricultural technology applications (IPB Digitani and Agricount), and character development of school-age children using the cooperative based learning method. As a result, this activity succeeded in achieving its target with a positive response from the community, where more than 60% of participants felt very satisfied. The programs implemented provided direct benefits in the form of increasing soil fertility, pest control, access to agricultural technology information, and strengthening children's character. This activity shows that the programs implemented are effective in supporting community empowerment and contributing to village sustainability. Recommendations include further training, program integration into the curriculum, and strengthening cooperation with partners are needed for program sustainability.